Validation of faster joint control strategy for battery and supercapacitor based energy storage system - Manandhar, Ujjal (2019)
Energy storage system (ESS) is generally used to manage the intermittency of the renewable energy sources (RESs). The proper control strategy is needed to effectively maintain the power balance between the RESs, load demand, and ESS. The conventional control strategy for the hybrid energy storage system (HESS) uses the high-/low-pass filter method for system net power decomposition and the ESS power dispatch. In this paper, a new joint control strategy is proposed for photovoltaic (PV) based DC grid system, with battery and supercapacitor (SC) as a HESS. The new joint control strategy utilizes the uncompensated power from the battery system to increase the performance of the overall HESS. The advantages of the proposed control strategy over the conventional control strategy are faster DC link voltage restoration and effective power sharing between the battery and the SC. The detailed stability analysis of the proposed control strategy is also presented. The effectiveness of the proposed control strategy over the conventional control strategy is validated with the short-term and long-term experimental studies.